PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pardede, Rismawaty; Siregar, Liper; Tarigan, Parman; Supitriyani, Supitriyani (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The purpose of this research is to know the description of liquidity, profitbility and firm’s values and the effect of liquidity and profitability of firm’s value at Company Sub Sector Building and Contruction listed on the Indonesia Stock Exchange. The research design in this research is a library research and technique analysis in this research as: assumption classic test, qualitative and quantitative descriptive analysisThe regression is Ŷ = 8,871 – 4,778X1 + 13,343X2. Correlation coefficient of r = 0,654 and RSquare of 42,7 %. Simultaneous test results is Fcount>Ftable (11,947>3,29) or significance level 0,000<0,05 means liquidity and profitability has significant effect on firm’s value at Company Sub Sector Building and Contruction listed on the Indonesian Stock Exchange. The t-test results show liquidity has tcount<ttable or 4,471>2,03693 or significance level 0,000<0,05, means liquidity has significant effect on firm’s value at Company Sub Sector Building and Contruction listed on the Indonesian Stock Exchange. The t-test results that profitability to tcount>ttable (3,451>2,03693) or significance level 0,00<0,05, profitability has significant effect on firm’s value at Company Sub Sector Building listed on the Indonesian Stock Exchange.The result of this research suggests that company should improve managment should pay more attention to liquidity and profitability as a way to enhance shareholder value in addittion. Keywords: Liquidity, Profitability, and Firm’s Value